1988
DOI: 10.1029/ja093ia06p05505
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the GSFC Q3 model for trapped particle motion

Abstract: The adiabatic motion of energetic charged particles in the Uranian magnetosphere is studied by numerical computation of field geometric invariants associated with the GSFC Q3 magnetic field model. Comparison of the computed L shell values along the Voyager 2 trajectory with those associated with the Uranian satellites Ariel, Umbriel, and Miranda as a function of their orbital position allows the prediction of times and locations where absorption effects of charged particles should be observable. Systematic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Also shown on these trajectory plots are 1-hour UT time ticks along the trajectories, vertical dashed lines that show the "average" minimum L shell positions of the seven satellites (Triton and 1989N1 Table 2]). The Uranus encounter showed that the minimum L value of a satellite is where particle features are expected [Mauk et ah, 1987;Stone et al, 1986;Acuna et al, 1988]. The situation is not yet clear for rings [e.g., Paranicas and Cheng, this issue (a)].…”
Section: Voyager 2 Trajectorymentioning
confidence: 99%
“…Also shown on these trajectory plots are 1-hour UT time ticks along the trajectories, vertical dashed lines that show the "average" minimum L shell positions of the seven satellites (Triton and 1989N1 Table 2]). The Uranus encounter showed that the minimum L value of a satellite is where particle features are expected [Mauk et ah, 1987;Stone et al, 1986;Acuna et al, 1988]. The situation is not yet clear for rings [e.g., Paranicas and Cheng, this issue (a)].…”
Section: Voyager 2 Trajectorymentioning
confidence: 99%
“…Also, a surprisingly large tilt (60 ø to the rotation axis) and offset (0.33 R t: from the planetary center) of the magnetic dipole axis were found along with an almost Sun-planet aligned rotation axis. The large tilted dipole has consequences such as large traversals of the Uranian moons over a wide range of magnetic latitudes and longitudes, resulting in peculiar particle absorption signatures [Mauk et al, 1987;Acuna et al, 1988]. The near Sun-planet aligned rotation axis leads to the speculation of a convection-dominated Uranian magnetosphere at the epoch during the V2 visit [Selesnick and Richardson, 1986;l/asyliunas, 1987].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the effect of using only the first two terms to calculate the predicted locations for absorption of energetic charged particles by the Uranian moons is significant, and the magnetic equator derived from the 03 model is warped and noticeably distorted from the plane surface associated with the OTD model lacuna et al., 1988]. The 03 model, however, cannot account for some significant discrepancies in the location of charged particle absorption signatures associated with the sweeping effects of the Uranian satellites [Acuna et al, 1988], nor can it explain why some H 2 band emissions fall partly outside the 03 auroral zone [Herbert and Sandel, 1994].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that maximum intensity was observed 7 min after reaching the Q3 minimum L is consistent with an expected latitudinal gradient (see section 5). However, the L value at the flux maximum is only 0.01 greater than that at minimum L. This observation provides a one-point test of Q3 values for L which were calculated with the approximation that drift shell splitting is negligible [Acufia et al, 1988]. Since the effects of high-order field components decline at larger distances from Uranus, we assume that the accuracy of drift shell positions calculated from Q3 is better than AL --• 0.01 in the macrosignature regions where we localize positions of intensity minima in L.…”
Section: Spacecraft and Satellite Coordinatesmentioning
confidence: 99%